Evaluation of the Effect of Black Soldier Fly Larvae Meal on the Growth of Aquatic Species: A Literature Review - Zambrano-Vera, David-Agapito; Alcívar-Bazurto, Martha-Cecilia; Gómez-Zurita, Susy-Natalia; Vinocunga-Pillajo, Reni-Danilo; Romero-Vistín, Aida-Salomé; Sánchez-Vallejo, Carlos-Alfonso (Revista Colombiana de Ciencias Pecuarias, 2025)
Background: Given the growing need to feed a projected population of 9.6 billion by 2050, it is crucial to explore protein sources for the aquaculture industry. Objective: The objective of this article was to identify the nutritional and growth effects observed in aquatic species fed with black soldier fly larvae meal (BSFLM) through a literature review. Methods: A systematic literature review was conducted following PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. The research for relevant studies was carried out on June 10, 2024, using databases such as ScienceDirect, Google Scholar, SciELO, and MDPI. Results: The results indicate that the inclusion of BSFLM in aquaculture diets can replace up to 100% of soybean meal in species such as juvenile grass carp (Ctenopharyngodon idellus) without significantly affecting final body weight or specific growth rate (SGR). In tilapia (Oreochromis niloticus), the inclusion of 20% BSFLM resulted in a significant increase in daily weight gain, improving the biosynthesis of fatty acids and amino acids. For white shrimp (Litopenaeus vannamei), an inclusion of up to 22.5% BSFLM had no negative impact on specific growth rate or feed efficiency. In Atlantic salmon (Salmo salar), the inclusion of up to 8% BSFLM did not adversely affect growth or feed performance. Conclusion: BSFLM can replace up to 61.3% of fishmeal and 95.4% of fish oil, using fewer resources